Performing Qadhā Prayer on Behalf of the Deceased: Hadith Study and Jurisprudential Analysis of the Four Madhhabs - Ali Yusuf Muzaki; Ahmad Mukhlish Sirojuddin; Hafidhul Mubarok; Ridwan; Muthohharun Afif (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study investigates the Islamic jurisprudential status of prayers left unperformed (qadha shalat) by a deceased Muslim, combining rigorous hadith authentication (takhrij) with cross-madhhab legal comparison (muqaranah al-madzahib). The central question — whether a guardian (wali) may perform substitute prayers on behalf of the deceased by analogy with authenticated fasting-substitute hadiths — has generated sustained scholarly disagreement across the four Sunni schools. Drawing on primary classical sources and recent scholarship in Islamic law, including Scopus-indexed journals and nationally accredited Indonesian journals , this article demonstrates that: (1) no explicit (sharih) sahih hadith authorizes qadha prayers by a guardian; (2) the juristic disagreement turns precisely on competing definitions of the legal cause ('illah) in the qiyas argument, not on the hadith texts themselves; and (3) the Hanbali dissenting position, though methodologically coherent, is based on an 'illah —